A Connected Curriculum for Higher Education - Fung, Dilly (UCL Press, 2017)
Is it possible to bring university research and student education into a more connected, more symbiotic relationship? If so, can we develop programmes of study that enable faculty, students and 'real world' communities to connect in new ways? In this accessible book, Dilly Fung argues that it is not only possible but also potentially transformational to develop new forms of research-based education. Presenting the Connected Curriculum framework already adopted by UCL, she opens windows onto new initiatives related to, for example, research-based education, internationalisation, the global classroom, interdisciplinarity and public engagement.